Implementasi Sensor Piezoelectric Sebagai Prototype Alat Musik Piano Berbasis Arduino UNO - Kiki M. Rizki; Rizal Maulana; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Microcontroller technology in these day improves musical instrument variety and it's quality in terms of the ease in studying musical instrument. One of the popular musical instrument that mostly made into virtual musical is a piano. The piano that combined with microcontroller technology have some advantages, they are flexible and more economical than the conventional piano. It flexibility can be showed with piezoelectric sensor with MIDI (Musical Instrument Digital Interface) addition that allows musician to record a digital sound. Piezoelectric sensor captures vibrations from surface that resulted from hand tapping, then converts them into electrical voltage, so it suitable for virtual piano implementation. The electrical voltage from piezoelectric later to be processed by a microcontroller to produce output sound. Arduino UNO as microcontroller is using C/C++ programming to execute programs. The program works successful as desired by our indicator. According to the test for output system comparing to a real piano, the average of frequency comparison is 0,76 Hz with 0,21% error.